EARLY TO MIDDLE MIOCENE TURTLES FROM THE NORTHERNMOST TIP OF SOUTH AMERICA: GIANT TESTUDINIDS, CHELIDS, AND PODOCNEMIDIDS FROM THE CASTILLETES FORMATION, COLOMBIA (Ameghiniana, 2014)
Here we describe the northernmost South American record of fossil turtles from the late early Miocene to early middle Miocene of the Castilletes Formation, on the Alta Guajira Peninsula, Cocinetas basin, Colombia. Turtles in the lower segment of the Castilletes Formation (c. 16.33 Ma) are pleurodires or side-necked turtles belonging to Chelus colombiana Wood, Chelus sp., and Podocnemididae incertae sedis, and cryptodires or hidden-necked turtles attributed to Chelonoidis sp., all of them characterized by the large size of their shells, 1 meter or more total length. The middle segment of the formation (c. 14 Ma) contains specimens of Podocnemididae incertae sedis and Chelonoidis sp. The turtle fauna from Castilletes share taxa with faunas from La Venta (middle–late Miocene of Colombia), Urumaco, and Western Amazonia (late Miocene from Venezuela, Brazil, and Peru); all of these records indicate a wider geographical distribution for podocnemidids, chelids, and testudinids of tropical South America during the early to middle Miocene. The large size of the fossils described here also confirms that gigantism was characteristic of South American tropical turtles during the early Miocene, a trend that lasted at least from the Paleocene to the Pliocene in different lineages. Resumen. TORTUGAS DEL MIOCENO TEMPRANO A MEDIO EN EL EXTREMO MÁS SEPTENTRIONAL DE SURAMERICA; TESTUDÍNIDOS GIGANTES, QUÉLIDOS, Y PODOCNEMÍDIDOS DE LA FORMACIÓN CASTILLETES, COLOMBIA. En este artículo describimos el registro fósil de tortugas de la parte tardía del Mioceno temprano a la parte temprana del Mioceno medio en el extremo más septentrional de Suramérica, en la Península de la Alta Guajira, Cuenca de Cocinetas, Colombia. Las tortugas del segmento más inferior de la Formación Castilletes (c. 16.33 Ma) pertenecen a pleurodiras o tortugas que retraen el cuello en forma lateral que incluyen a: Chelus colombiana Wood, Chelus sp., y Podocnemididae incertae sedis, y las cryptodiras o tortugas que retraen el cuello en forma vertical, atribuidas al género Chelonoidis sp. Todas estas tortugas están caracterizadas por el gran tamaño de sus caparazones de 1 metro de longitud o más. En el segmento medio de la Formación (c 14 Ma) solo se encontraron Podocnemididae incertae sedis y Chelonoidis sp. La fauna de tortugas de la Formación Castilletes comparte taxones con la fauna de La Venta (Mioceno medio de Colombia), y con la faunas de Urumaco y el Oeste Amazónico (Mioceno tardío de Venezuela, Brasil y Perú), indicando una distribución geográfica más extensa de los podocnemídidos, quélidos, y testudínidos de la parte tropical de Suramérica durante el Mioceno temprano a medio. El gran tamaño de los fósiles descritos aquí confirma que el gigantismo fue una característica de las tortugas tropicales de Amé- rica del Sur también durante el Mioceno temprano, una tendencia que duró al menos desde el Paleoceno hasta el Plioceno en diferentes linajes.